Evaluation of the surgical approach in urethroplasty and glanuloplasty according to “Duplay approach” for hypospadias patients - الدالي مضر; حسان ناصر; لؤي نداف (Latakia University Journal -Medical Sciences Series, 2023)
Objective: The aim of the research is to evaluate the surgical approach in urethroplasty and glanuloplasty according to “Duplay approach” for hypospadias patients in Tishreen University Hospital between 1/1/2018 and 1/1/2022. Methods: Study type: A Prospective and Retrospective Observational Study The research sample consisted of (40) pediatric patients who attended Tishreen University Hospital with hypospadias and who underwent surgical repair using the Duplay method, Where the patient was evaluated before the surgery and evaluated the surgery and follow-up after. Results: The patients were divided into three age groups to facilitate the study of the results and emphasizing the importance of choosing the appropriate time for surgical repair, as the largest percentage was for children between 3 -5 years (52.5%). We divided them into groups according to the degree of hypospadias, where the largest percentage of sub coronary hypospadias was (47.5%). All patients underwent surgery and during surgery, a Nelaton catheter for urinary drainage was chosen, the most used size was 8Fr in 28 patients (70% of the research sample). An incision of the urethral plate has been made in 38 patients (95%). (PDS 6-0) suture was used to manufacture the urethra and glans in 36 patients (90%). The functional results were evaluated, and the urine flow was direct anterior in (85%) of the patients, while a divergence or bisection of the urine flow was found in (15%). However, in the following reviews, one patient had a bisection in the urine stream and a divergence in three patients. As for the irritation symptoms, they were present in 4 patients after the removal of the urinary catheter, and remained present in the third review in only one patient. Obstructive symptoms were present in 6 patients after removal of the urinary catheter, and remained present in only two patients in the third review. Postoperative complications were also evaluated. Meatal stenosis was found in 4 patients (10%). The Urethrocutaneous fistula was found in 3 patients (7.5%). Conclusions: Duplay approach in urethroplasty and glanuloplasty for the patients with hypospadias as a good method with Few complications, good functional results, and good visual appearance. We recommend the need to use accurate surgical tools for hypospadias operations, and choose the appropriate time for surgical repair.